The return of Religious Education to the public schools: a discussion between secularized liberals and a Romanized Bishop 1883-1892 - Sandí Morales, José Aurelio (2019)
The intend of this article is to provide a more detailed insight during the process of restoring the religious education to public schools in Costa Rica after it was excluded from the educational system because of the laws issued from 1884 to 1886 that were responsible of this exclusion. But before explaining the mentioned topic, it will be given a short overview about the educational system in Costa Rica starting in the colonial period up to 1884 in order to understand not only the Catholicism´s role played during this time frame, but also the episcopal claim regarding this arbitrary exclusion in 1884. This endeavor was leaded by Mgr. Thiel, second bishop from the Costa Rican diocese, with the help of the clergy and the Catholic members they had the conviction of avoiding the secularization of the Costa Rican society (this secularization was proposed by the liberal positivists who ruled the country after 1882), Mgr. Thiel made all kind of efforts to restore the religious education to the state schools. Keywords: religion, education, Church, State, romanization